Predictors of Inadequate Bowel Preparation and Salvage Options on Colonoscopy - Ju Sung Sim; Ja Seol Koo (Clinical Endoscopy, 2016)
Inadequate bowel preparation is observed in more than 25% of all colonoscopies. Identification of predictive factors for inadequate colon cleaning is helpful and more detailed preparation methods should be used for patients at high risk. Age, male sex, inpatient status, and comorbidities were identified as independent risk factors in several previous studies. In patients with insufficient colon preparation, colon irrigation with endoscopic pumps or next-day colonoscopy following further bowel cleaning should be performed. In order to improve the efficacy and safety of both bowel preparation and colonoscopy, the endoscopic team should identify the patient’s medical conditions and choose the optimal bowel preparation agent and regimen.